Evaluation of Anti-VEGF and Pan-Retinal Photocoagulation Laser Therapies in Proliferative Diabetic Retinopathy Patients: A Systematic Review - Indrakila, Senyum; Imani, Namira Putri; Asaduddin, Aiman Hilmi; Karima, Muzakiya Lailatul; Widjaja, Lygia Angelica (Pharmaceutical Sciences and Research, 2023)
Diabetic retinopathy is a complication of diabetes that is one of the top five causes of blindness in those over 50. The standard treatment is pan-retinal photocoagulation, which is effective but has established side effects. Anti-vascular endothelial growth factor (anti-VEGF) therapy becomes an alternative to avoid the side effects caused by laser therapy. This systematic review aims to know the effectiveness of anti-VEGF therapy compared to the pan-retinal photocoagulation laser therapy in patients with proliferative diabetic retinopathy. This review was carried out using a systematic review checklist on PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses). The articles reviewed were randomized controlled trial articles that met the inclusion and exclusion criteria. Based on inclusion and exclusion criteria, six articles were selected from a total of 215. Patients who received anti-VEGF medication had better visual acuity (positive values), whereas patients who received laser therapy had poorer visual acuity (negative values). Those results are because the laser directs light towards the retina, damaging photoreceptors and retinal cells as well as reducing visual acuity. On the contrary, anti-VEGF prevents damage to retinal endothelial cells and blood leaks in the vitreous by decreasing VEGF expression and thus resulting in improved visual acuity. Anti-VEGF proved to be a more practical alternative therapy in improving visual acuity than pan-retinal photocoagulation for patients with proliferative diabetic retinopathy.